(3E, 7E)-3, 7-Bis(2-oxoindolin-3-ylidene)-5, 7-dihydropyrrolo[2, 3-f]indole-2, 6(1H, 3H)-dione based polymers for ambipolar organic thin film transistors1. Issue 38 (11th May 2015) - He, Yinghui; Guo, Chang; Sun, Bin; Quinn, Jesse; Li, Yuning
<x xml:space="preserve">Abstract</x> A novel acceptor, (3E, 7E)-3, 7-bis(2-oxoindolin-3-ylidene)-5, 7-dihydropyrrolo[2, 3-f]indole-2, 6(1H, 3H)-dione, is synthesized and used for donor–acceptor polymer semiconductors.